Redox Regulator GLRX Is Associated With Tumor Immunity in Glioma - Chang, Yuanhao; Li, Guanzhang; Zhai, You; Huang, Lijie; Feng, Yuemei; Wang, Di; Zhang, Wei; Hu, Huimin (Frontiers in Immunology, 2020)
Glutaredoxin is central to cellular redox chemistry, and regulates redox homeostasis and malignant progression of many cancers. In glioma, the role of its coding gene (GLRX) remains unclear. We aimed to elucidate the role of glutaredoxin at the transcriptome level and its clinical prognostic value in glioma. In total, we evaluated 1,717 glioma samples with transcriptome data and corresponding clinical data, as well as single-cell sequencing data from 6 glioma patients, from publicly available databases. Gene Set Variation Analysis and Gene-Ontology Analysis were performed to reveal the biological function of GLRX. Immune cell enrichment score was calculated by CSVA analysis. Single-cell sequencing data was visualized by t-distributed Stochastic Neighbor Embedding analysis. The prognostic value of GLRX in glioma was verified by the Kaplan-Meier curve and multivariate COX analysis. GLRX was found to be highly enriched in gliomas of higher grades with wildtype IDH, without 1p/19q co-deletion, and with methylated MGMT promoter. Moreover, GLRX could be a potential marker for mesenchymal molecular subtype of gliomas. The expression of GLRX was closely related to the tumor immune process, immune checkpoints, and inflammatory factors, with GLRX being specifically expressed in M0 macrophages. GLRX also showed to be an independent prognostic factor in glioma. Altogether, our study outcomes show that GLRX is highly enriched in malignant gliomas and is closely related to the tumor immune microenvironment. Therefore, GLRX-targeted cell redox regulatory therapy may enhance the efficacy of glioma immunotherapy.